A 36 kg Giant Ovarian Fibroma with Meigs Syndrome: A Case Report and Literature Review of Extremely Giant Ovarian Tumor - Miyu Tanaka; Koji Yamanoi; Sachiko Kitamura; Naoki Horikawa; Yoshitsugu Chigusa; Akihito Horie; Ken Yamaguchi; Junzo Hamanishi; Eiji Kondoh; Masaki Mandai (Hindawi Limited, 2021)
Ovarian tumors can get extremely giant to occupy the whole abdominal cavity. We report a case of 36 kg solid ovarian tumor, which was the largest ovarian solid tumor that have been ever reported. A 54-year-old woman presented to our hospital with a chief complaint of markedly distended abdominal wall. Preoperative imaging examinations revealed that most of the tumor was uniform and its density was like that of subcutaneous fat. Pleural effusion was detected in the right thoracic region. We organized a multidisciplinary team and successfully resected the right adnexa. The patient had an uneventful postoperative course, and she was discharged on the 7th postoperative day and diagnosed with a fibroma of the ovary with Meigs syndrome. A comprehensive literature search revealed 48 cases of extremely giant ovarian tumor in these 20 years. Six out of 48 cases are solid. Twelve out of 48 cases are malignant or borderline malignant, and patients' age and tumor size/weight were not related to the frequency of malignancy/borderline malignancy. As many as 4 out of 48 patients died before their first hospital visit or early after surgery. Clinicians should consider a considerable high mortality and frequency of severe surgical complications when planning the treatment strategy for extremely giant ovarian tumors.